ANALYSIS OF SHOE ORDERING PATTERN AT PT. PRATAMA ABADI INDUSTRI USING THE APRIORI ALGORITHM - Retno Wati; Imron Imron; Albert Riyandi (LPPM Nusa Mandiri, 2021)
Inventory is one of the most important factors in ensuring the continuity of the production process. PT. Pratama Abadi Industri is an industrial company in the field of shoe sales. In its activities, PT. Pratama Abadi Industri was unable to provide production materials appropriately, causing a shortage of shoe material stock for the production of the type of shoe that the customer is most interested in. The method used in this research is to use the a priori Algorithm and to get accurate results, this research uses the Tanagra 1.4.50 software. The purpose of this study was to analyze the ordering of NIKE shoes that are often ordered by customers by looking at their previous order patterns. This a priori algorithm can produce 7 final association rules between items with a minimum value of 30% of support and a minimum of 70% of confidence and from May 2020 to October 2020 it is known that the most popular order pattern for NIKE shoes is NIKE shoes with the Tailwind (100%), Revolution 5 (100%), Air Max Plus (100%) and Classic Cortez Leather (100%) which can be used as reference materials in determining the next production material inventory.